2020
DOI: 10.1097/md.0000000000019802
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pneumonia in patients with anti-NMDA receptor encephalitis

Abstract: To identify the risk factors of pneumonia in patients with Anti-N-methyl-D-aspartate (Anti-NMDA) receptor encephalitis. This is a retrospective study. Department of Neurology in West China Hospital of Sichuan University. Patients with a definitive diagnosis of anti-NMDA receptor encephalitis. Risk factors associated with pneumonia were examined by bivariate analysis and multivariate logistic regression model. A total of 104 patients were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…NMDAR antibodiesmediated GABA dysfunction can cause frontostriatal syndrome and brainstem disinhibition (17), resulting in patients with MDs, autonomic dysfunction, and various sleep problems before onset, throughout the disease, and even after recovery (23). Therefore, (24) study found that abnormal movements were an independent risk factor for the development of pneumonia (odds ratio = 3.716, 95% confidence interval = 1.149-12.015, p = 0.028). We consider the following reasons for the above finding may be as follows: firstly, OFLD involving the mouth, tongue, and face is the most common MD, which can affect the oral phase of the normal swallowing process (25), and may lead to dysphagia and aspiration.…”
Section: Discussionmentioning
confidence: 98%
“…NMDAR antibodiesmediated GABA dysfunction can cause frontostriatal syndrome and brainstem disinhibition (17), resulting in patients with MDs, autonomic dysfunction, and various sleep problems before onset, throughout the disease, and even after recovery (23). Therefore, (24) study found that abnormal movements were an independent risk factor for the development of pneumonia (odds ratio = 3.716, 95% confidence interval = 1.149-12.015, p = 0.028). We consider the following reasons for the above finding may be as follows: firstly, OFLD involving the mouth, tongue, and face is the most common MD, which can affect the oral phase of the normal swallowing process (25), and may lead to dysphagia and aspiration.…”
Section: Discussionmentioning
confidence: 98%
“…Severe movement disorders and autonomic instability often necessitate a prolonged intensive care unit stay. Hospital-associated complications are common, including ventilator-associated pneumonia in approximately 50% of all admissions, urinary tract infections and catheter-related bloodstream infections 16 17. Despite the severity of most presentations, up to 70% of patients will recover, although with the possibility of disease relapse in approximately 15% of survivors 9 18.…”
Section: Discussionmentioning
confidence: 99%